Youth sports training service quality determinants analysis - Zagorodnikova, A. Y.; Stepanova, O. N.; Shalupin, V. I.; Kumantsova, E. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze and rank the youth sports training service quality determinants.